Quality and Productivity Management of Design Activities in Construction: A Dynamic Approach and Digital Tools - DEMIDOVA, Olena; VAKHOVYCH, Dmytro (Ways to Improve Construction Efficiency, 2025)
The article explores the pressing scientific and practical problem of enhancing the productivity of design organizations and the comprehensive quality management of project documentation in the context of the global digitalization of the construction industry. The relevance of the topic is driven by the urgent need for rapid and high-quality infrastructure reconstruction against the backdrop of limited qualified resources and the risk of losing unique intellectual capital due to the generational shift of designers. It is substantiated that traditional design organization methods, which rely exclusively on the intuitive experience of specialists and basic computer-aided design (CAD) systems, have exhausted their potential and cannot ensure the required level of productivity. The authors propose a paradigm shift in the perception of project documentation quality, viewing it not as a static set of technically correct drawings, but as a dynamic digital asset. An original four-component integrated quality model has been developed, encompassing: regulatory and legal validity (compliance with state building codes and standards); technical and operational excellence (absence of clashes according to the 1:10:100 rule); consumer-value fitness (maximization of the economic and functional efficiency of the facility); and information-digital maturity (compliance of the level of information detail of attributive data with information modeling requirements). To objectify the control process, a mathematical model of an integrated quality index Iq has been developed, formed on the basis of weighting coefficients for expert validity, operational accuracy, digital completeness, and a multi-stage coefficient of consumer value. A specific feature of the proposed methodology is the treatment of consumer quality as a time-variable value, evaluated at three stages of the project life cycle: upon documentation approval, after construction completion, and during the actual operation of the facility. The innovative concept of the "quality delta" ΔI is introduced — representing the difference between the predictive quality index at the documentation issuance stage and the actual index during operation. It is proven that in traditional design, this delta is critically high due to the emergence of unforeseen geometric clashes and operational defects. As an effective practical tool to solve this problem, the development and implementation of specialized Project Design Plugins (PDPs) based on the Knowledge-Based Engineering (KBE) methodology are proposed. It is proven that the PDP allows for the algorithmization of the implicit heuristic experience of the designer, creating tangible digital capital for the organization. The use of PDPs ensures the automated generation of solutions with built-in regulatory control (Code Checking), a priori collision-free coordination (Clash Detection), and multi-criteria optimization. The application of predictive analysis algorithms minimizes the quality delta, making the predictive indicators of the documentation identical to its actual realization. This ensures a radical reduction in the time required to review solutions, the elimination of routine operations, and an exponential growth in the overall productivity of design activities in construction.